2008
DOI: 10.1007/s00540-007-0572-4
|View full text |Cite
|
Sign up to set email alerts
|

Olprinone decreases elevated concentrations of cytokine-induced neutrophil chemoattractant-1 in septic rats

Abstract: Olprinone decreases elevated CINC-1 concentration in the diaphragm under septic conditions. This suggests that olprinone may inhibit neutrophil recruitment to the diaphragm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…However, a previous study showed that serum MCP-1 levels are raised in septic patients and are even higher in those with severe sepsis ( 31 ) . Also, MCP-1 and CINC-1 were significantly increased in a severe inflammatory reaction as found in thermal injury and caecal ligation and perforation in rats ( 32 , 33 ) . The discrepancies among the studies may have resulted from the time required to take the measurement and the duration and location of these mediators exist in biological fluids.…”
Section: Discussionmentioning
confidence: 86%
“…However, a previous study showed that serum MCP-1 levels are raised in septic patients and are even higher in those with severe sepsis ( 31 ) . Also, MCP-1 and CINC-1 were significantly increased in a severe inflammatory reaction as found in thermal injury and caecal ligation and perforation in rats ( 32 , 33 ) . The discrepancies among the studies may have resulted from the time required to take the measurement and the duration and location of these mediators exist in biological fluids.…”
Section: Discussionmentioning
confidence: 86%
“…No reports have addressed the role for olprinone in pathophysiology of SCI. Interestingly, olprinone reduces the IR-induced acute renal injury in rats through enhancement of cAMP, inhibition of leukocyte activation [19], and decreasing elevated concentrations of cytokine-induced neutrophil chemoattractant-1 in septic rats [20].…”
Section: Introductionmentioning
confidence: 96%